Regenerando un asentamiento amenazado por riesgos antropicos-Vivienda en Lima, Peru. (2024)
The dynamics of the half part of an intervention that is decided to participate in a competition at the Pan-American Observatory landscape, land and architecture (OPPTA) in emergency interventions. It shares held in various locations in Latin America, including Lima, Peru. The interest of the competition was to develop strategies to improve critical conditions of natural effects and take action triggers for the entire place. Based on a key question of how to regenerate a settlement threatened by anthropogenic risks?, Is to formalize a proposal to rehabilitate the land, infrastructure endowment, prevent most natural disasters, active and social relations of the territory lost identity.